Феминистическая методология как политика образования: конструирование новых гендерных идентичностей в украинской высшей школе - Суковатая, В. (Социология: теория, методы, маркетинг, 2007)
The author suggests some ideas embodied in a series of lectures, such as "Woman and Culture: Gender Aspects", "Feministic Conceptions in the Visual Arts and Cinema:Gender Analysis of Aesthetics", "The Image of Love in the World Culture: Gender Analysis of the National Philosophies of Marriage and Sexuality". The lectures (also known as gender courses) have been given to the students of V.N.Karazin Kharkiv National University during 1996—2006.